Hydrated lime and cockle shell ash: A sustainable approach to soft kaolin clay improvement - Nik Noor Atyrah, Nik Aziz; Muzamir, Hasan; Muhammad Syamsul Imran, Zaini; Siti Nor Aida, Mohamed; Winter, Michael James (Semarak Ilmu Sdn. Bhd., 2025)
Kaolin clay is characterized by poor permeability and low shear strength, making it unsuitable for construction. Hydrated Lime (HL) and Cockleshell Ash (CSA) as eco- friendly stabilizing agents were utilized to improve the construction-related properties of kaolin clay. The research explores the effectiveness compound between HL and CSA on the soil's geotechnical characteristics, including Density ratio, plasticity measure (PI), peak dry density (MDD), and ideal moisture level (OMC), and unconfined compressive strength (UCS). Initially, kaolin clay was stabilized with 2%, 4%, and 6% HL to determine the optimum HL content based on UCS. Following this, CSA was incorporated at 3%, 6%, and 9% to evaluate its complementary effect alongside HL. A comprehensive set of laboratory tests, including mechanical Sieve analysis, hydrometer test, specific gravity test, Atterberg limits, standard proctor test, and unconfined compression test, were executed on the sample of altered and unaltered kaolin clay. The results demonstrate that the combined use of HL and CSA significantly reduces specific gravity, lowers the plasticity index, decreases MDD, and reduces OMC, while leading to a substantial increase in UCS. In comparison to untreated kaolin and soil stabilized with HL alone, the HL-CSA mixtures exhibit superior improvements in shear strength and compressibility. The optimized HL-CSA blend provides an environmentally conscious and viable remedy for enhancing the geotechnical properties of kaolin clay, offering promising applications for construction and geotechnical engineering project.